2004
DOI: 10.1024/0301-1526.33.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Early carotid endarterectomy in patients with a nondisabling ischemic stroke: Results of a retrospective analysis

Abstract: Our results suggest that selected patients with a minor stroke (mRS < or = 2 on admission) can safely undergo early CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…The timing of surgery does not seem to influence the benefit of the CEA.'' Wolfle and coworkers [21] note similar results in a retrospective series of 66 patients who were neurologically stable and undergoing CEA for greater than 50% symptomatic stenosis after a mean interval of 10 days post stroke. They reported an operative mortality of 0% and (mostly) transient neurologic worsening in 5 (12.1%) patients, with resolution of symptoms within 4 days in 80%.…”
Section: Background Regarding Delayed Surgerysupporting
confidence: 62%
See 1 more Smart Citation
“…The timing of surgery does not seem to influence the benefit of the CEA.'' Wolfle and coworkers [21] note similar results in a retrospective series of 66 patients who were neurologically stable and undergoing CEA for greater than 50% symptomatic stenosis after a mean interval of 10 days post stroke. They reported an operative mortality of 0% and (mostly) transient neurologic worsening in 5 (12.1%) patients, with resolution of symptoms within 4 days in 80%.…”
Section: Background Regarding Delayed Surgerysupporting
confidence: 62%
“…In their series of 66 patients undergoing CEA after stroke, Wolfle and coworkers [21] note, ''no correlation between timing of surgery or the presence of acute ipsilateral cranial CT defects with the occurrence of postoperative stroke.'' Similarly, in their study of 200 patients undergoing CEA within 6 months of a stroke, Paty and colleagues [13] note, ''no correlation between timing of surgery, extent of infarct on computed tomography/magnetic resonance imaging, and postoperative neurologic complications with the occurrence of postoperative stroke.''…”
Section: Imaging Findings and Their Relationship To The Timing Of Surmentioning
confidence: 98%
“…[4][5][6] Because the study populations and the questions of interest were similar among the 3 trials, we performed a combined data analysis to achieve an adequate number of patients and increase the statistical power.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, recent studies have emphasized the safety of early CEA in patients with nondisabling stroke or acute neurologic events. [3][4][5][6][7] Moreover, previous reports on early CEA 8,9 have shown that expedited carotid revascularization can improve neurologic outcome, as evaluated by the National Institutes of Health Stroke Scale (NIHSS), probably recruiting brain areas that can be reperfused before cell death occurs. The aim of this prospective study was to evaluate the safety and benefit of urgent CEA in a consecutive series of patients presenting with carotid disease and a mild or moderate acute stable neurologic event.…”
mentioning
confidence: 99%